The relationship of coaching behavior towards the motivation of football athletes in Malaysia sports’ school / Nurhasni Mohd Noor … [et al.] - Mohd Noor, Nurhasni; Hassan, Mohamad Faithal; Soh, Kim Geok; Seruti, Jane Francisca (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
This study is aimed to compare coaching behavior among football coaches and to determine its’ effects on the motivation of football athletes in Malaysian sports’ school  A total of 123 football athletes (mean age = 15.30 years, SD = 1.61 years) from three different sport schools were chosen using the simple random sampling method. The survey used Coaching Behavior Scale for Sport (CBS-S) to measure coaching behavior and Sport Motivation Scale (SMS) to measure the athletes’ motivation. Descriptive and inference analysis, one-way ANOVA and regression analysis were used to analyze the collected data. The results showed that there are significant differences in coaching behaviors among the football coaches in six out of seven dimensions of coaching behaviors. There are also significant differences showed in two out of the seven types of motivation and there are significant relationships between four coaching behaviors dimensions and six types of motivation and only negative personal rapport significantly associated to motivation. The Regression analysis result shows that physical training and planning has significant, dominant influence on identified extrinsic motivation (β = .31, p < .05) and external regulation extrinsic motivation (β = .34, p < .01). Meanwhile, negative personal rapport (β = .42, p < .01) has a dominant influence on amotivation. This study suggests that coaches should give attention the identified dominant influence factors in coaching behavior during training and competition.